Shifting the tax burden away from labour towards inheritances and gifts: Simulation results for Germany - Andreas Thiemann; Diana Ognyanova; Edlira Narazani; Balazs Palvolgyi; Athena Kalyva; Alexander Leodolter (European Commission, Joint Research Centre (JRC), 2021)
Germany's tax system places a relatively strong emphasis on direct taxes, particularly on labour. At the same time, revenues from the inheritance and gift tax are relatively low. This points towards a large-scale transfer of wealth from one generation to the next that is largely untaxed and thereby maintaining the high degree of wealth inequality observed in Germany. This is due mainly to the wide-ranging tax exemptions for business assets, which make the system complex, inefficient and regressive. This paper presents three hypothetical budget-neutral scenarios of broadening the inheritance and gift tax base while reducing the tax burden on labour income. Keeping the current progressive rates but abolishing tax exemptions would lead to about EUR 9-12 billion additional annual inheritance and gift tax revenue. Replacing the current tax regime by a flat rate of 10% or 15% could yield about EUR 0.5-2.3 billion or EUR 4-6.5 billion. Using EUROMOD, the microsimulation model of the EU, we show that these additional revenues could be used to reduce the tax burden on labour, which would improve income equality. Furthermore, estimations of labour supply responses to these reforms, based on the EUROLAB labour supply model, indicate that lowering the tax burden on labour may also lead to a slight increase in labour supply in particular for low-income earners.
Keywords: D31; H2; J2; 330; tax shift; inheritance and gift tax; tax wedge on labour; wealth inequality